Investigation and Enhancement of the Stability and Performance of Water Reduction Systems based on Cyclometalated Iridium(III) Complexes. Issue 1 (12th November 2012) - Hansen, Sven; Pohl, Marga‐Martina; Klahn, Marcus; Spannenberg, Anke; Beweries, Torsten
Abstract Water reduction systems that use a bis‐cyclometalated IrIII photosensitiser (PS) along with homogeneous Pd complexes as a source of in‐situ‐formed colloidal Pd as the water reducing complex (WRC) and triethylamine (TEA) as the sacrificial electron donor were tested and characterised with respect to their photocatalytic H2 production performance. It was confirmed that substitution of the 2‐(pyridin‐2‐yl)benzen‐1‐ide (pyb) ligand in the well‐known system [Ir(pyb)2(bpy)]+ (bpy=2, 2′‐bipyridine) by the fluorinated cyclometalating ligand 5‐fluoro‐2‐(5‐methylpyridin‐2‐yl)benzen‐1‐ide (Fmpyb) tremendously enhanced the H2 production rate. Moreover, variation of the bidentate N^N ligand bpy by alkyl substitution in the 4, 4′‐position resulted in an increase in the H2 production yield by a factor of three. The incident‐photon‐to‐hydrogen‐efficiency could be enhanced from 2.6 to 12.3 %. Furthermore, a new dinuclear Co complex was used as a reduction catalyst and showed up to 760 turnovers after 20 h. A detailed study of the concentration impact of all components in the photoredox system was performed. DFT calculations were used to aid the explanation of the findings.